2014
DOI: 10.1021/nl4038533
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ferromagnetism in Antiferromagnetic Cobalt Oxide Nanooctahedra

Abstract: Cobalt oxide octahedra were synthesized by thermal decomposition. Each octahedron-shaped nanoparticle consists of an antiferromagnetic CoO core enclosed by eight {111} facets interfaced to a thin (∼ 4 nm) surface layer of strained Co3O4. The nearly perfectly octahedral shaped particles with 20, 40, and 85 nm edge length show a weak room-temperature ferromagnetism that can be attributed to ferromagnetic correlations appearing due to strained lattice configurations at the CoO/Co3O4 interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 35 publications
5
78
1
Order By: Relevance
“…Remarkably, although the Néel temperature of Co 3 O 4 is below 40 K, the loop shifts persist up to ∼250 K or above, demonstrating the robustness of the exchange coupling between core and shell and the persistence of EB effects up to almost room temperature. Previous reports on the EB effect in systems with coexisting Co/Co 3 O 4 phases indicated that a minor presence of CoO led to the persistence of EB much above its T N [24][25][26][27][28][29]. Analogously, persistence of EB above T N was also observed in Co/FeF 2 [56] and was explained by retention of short range magnetic ordering above T N .…”
Section: Magnetic Characterizationmentioning
confidence: 64%
See 1 more Smart Citation
“…Remarkably, although the Néel temperature of Co 3 O 4 is below 40 K, the loop shifts persist up to ∼250 K or above, demonstrating the robustness of the exchange coupling between core and shell and the persistence of EB effects up to almost room temperature. Previous reports on the EB effect in systems with coexisting Co/Co 3 O 4 phases indicated that a minor presence of CoO led to the persistence of EB much above its T N [24][25][26][27][28][29]. Analogously, persistence of EB above T N was also observed in Co/FeF 2 [56] and was explained by retention of short range magnetic ordering above T N .…”
Section: Magnetic Characterizationmentioning
confidence: 64%
“…This process can be controlled under proper synthesis conditions to * oscar@ffn.ub.es; http://www.ffn.ub.es/oscar † sspsg2@iacs.res.in prevent further oxidation, leading to the formation of core/shell structures with the oxide phase (often an AF or ferrimagnetic material [22]) usually formed at the outer part of the structures. In the case of Co NP, most of the published studies [23] report the formation of the CoO phase on the shell, although in some cases the presence of the Co 3 O 4 has also been evidenced by structural [24,25] or magnetic characterization [26], The possibility of observing EB in Co based nanostructures in contact with Co 3 O 4 has been rather less investigated and the published studies focus on layered structures [27][28][29][30][31]. Synthesis of single phase CoO or Co 3 O 4 NP have been achieved by several authors, that have reported AF magnetic behavior with ordering temperatures reduced compared to the bulk values [32][33][34] and remanence values much higher than those for the bulk due to finite-size effects [26,35].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it is also possible to acquire high-resolution TEM (HRTEM) images, perform a fast Fourier transform (FFT), and obtain the inverse FFT image by selecting specific diffraction spots, i.e., a kind of computer-processed DF-TEM (see Fig. 2g-i) [191]. A further development of this technique allows also the quantitative evaluation of the internal strains in such core/shell nanoparticles.…”
Section: Morphologymentioning
confidence: 99%
“…Indeed, nanoparticles of AFM materials have non-zero magnetic moments and are therefore, strictly speaking, not AFM. [22][23][24][25] Numerous magnetization studies of AFM nanoparticles have shown that both the initial susceptibility and the magnetization in large applied fields are considerably larger than in the corresponding bulk materials. Néel justified this result due to the finite number of magnetic atoms in the nanoparticles, which may lead to a difference in the numbers of spins in the two sublattices because of the random occupancy of lattice sites.…”
Section: View Article Onlinementioning
confidence: 99%